ANALISIS PELAKSANAAN PRAKTIK KERJA LAPANGAN DALAM MEMPERSIAPKAN SISWA MEMASUKI DUNIA KERJA DI ERA REVOLUSI INDUSTRI 4.0 - Fatma Sukma Wardani (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The research aimed to find out: (1) On the Job Training implementation program  in Vocational High School 1 Karanganyar,  (2) readiness to  enter the world of work in Industrial Revolution 4.0 Era after implementation On the Job Training of students expertise competence Office Management Automation of Vocational High School 1 Karanganyar, (3) the constraints and solutions on implementation On the Job Training in preparing students to enter the world of work in Industrial Revolution 4.0 Era. This study is a descriptive qualitative research. There data source obtained from informant, place and event, as well as archive and document. The sampling techniques employed were purposive sampling and snowball sampling. Techniques of collecting data used were interview, observation, and documentation. The data validation was carried out using source and method triangulations. Techniques of analiyzing data used was an interactive model of analaysis. The result of research obtains (1) On the Job Training implementation in Vocational High School 1 Karanganyar going well and has positive role in preparing students to enter the world of work in industrial revolution 4.0 era. (2) Students readiness to enter the world of work in Industrial Revolution 4.0 Era after implementation of On the Job Training seen from compentencies needed such as IT knowledge and abilities, data and information processing and analytics, trust, self and time management, adabtability skills, follow the development of technology and want to learn, and communication skills (3) Implementation constraints such as the place less support skills needed on the world of work in Industrial Revolution 4.0 Era, distance of students place with On the Job Training location, incompatibility the type of  job that exists in the industrial world, discrepancy between the school and the industrial world, and difficulty on implementation a job in industrial world, while the solutions is location selection On the Job Training implementation, displacement On the Job Training location, synchronize curriculum and competencies, exploratory, and mentoring by teacher and the preceptor instructor